PELATIHAN PEMASARAN ONLINE PUSAT INKUBATOR WIRAUSAHA DAN KLINIK UMKM KOTA CILEGON - Agus David Ramdansyah; Stannia Cahaya Suci; Vadilla Mutia Zahara (Universitas Muhammadiyah Malang, 2021)
Small and Micro Enterprises (SMEs) has an important role in supporting the Indonesian economy. On the other hand, the internet has developed rapidly. This internet media progress can be utilized by SMEs to develop their business. However, in Indonesia, the number and presentation of MSEs that have used digital media is still very low. The use of the internet for the business world is can be seen in the product marketing process, for example the increasing online business in Indonesia, including in Banten, and is applied to all business activities. However, the use of the internet in SMEs in Banten is still very small. According to the 2016 Economic Census, only around 37 thousand businesses or 3.84 percent use the internet both for product marketing processes and others and only around 2.55 percent of the internet is used for marketing, this fact become the basis for training and strengthening for the community, especially for SMEs in Banten to realize how important it is to become